Factors Contributing to Formation and Existence of Community Identities in Bangkok Metropolis - Nutdhapol Chitchakkol; Yanin Rugwongwan; Chotewit Pongsermpol (My University, 2024)
In Bangkok, some traditional communities have maintained their identity despite urbanization. This research investigates the factors that influence the formation and existence of identities in three historic communities: Sam Phraeng, Talat Noi, and Soi Prachanaruemit (Wood Street). The research uses surveys, observations, and interviews to examine tangible and intangible elements. The results indicate that community identity originates from tangible elements such as architecture and landmarks, including intangible elements such as economics and society. Participation is essential to maintaining these identities, which requires effective community management, leading to income generation through activities and tourism that reflect the existence of community identities.
Keywords: Urbanization and City Planning